2020
DOI: 10.1002/sia.6846
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atomization on surface oxide composition in 316L stainless steel powders for additive manufacturing

Abstract: The initial oxide state of powder is essential to the robust additive manufacturing of metal components using powder bed fusion processes. However, the variation of the powder surface oxide composition as a function of the atomizing medium is not clear. This work summarizes a detailed surface characterization of three 316L powders, produced using water atomization (WA), vacuum melting inert gas atomization (VIGA), and nitrogen atomization (GA). X‐ray photoelectron spectroscopy (XPS) and scanning electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…113 Detailed surface-science studies combining SEM imaging, XPS, and TEM have further shown that the atomizing medium influences the surface oxide chemistry of 316L feedstock powders. 128 Specifically, the effects of vacuum induction melting, inert gas atomization, conventional nitrogen gas atomization, and water atomization on powder surface oxide chemistry were studied. Both sets of gas-atomized powders contained homogeneous Fe 2 O 3 oxide layers roughly 4 nm in thickness alongside other oxide inclusions.…”
Section: Influence Of Lpbf Feedstockmentioning
confidence: 99%
“…113 Detailed surface-science studies combining SEM imaging, XPS, and TEM have further shown that the atomizing medium influences the surface oxide chemistry of 316L feedstock powders. 128 Specifically, the effects of vacuum induction melting, inert gas atomization, conventional nitrogen gas atomization, and water atomization on powder surface oxide chemistry were studied. Both sets of gas-atomized powders contained homogeneous Fe 2 O 3 oxide layers roughly 4 nm in thickness alongside other oxide inclusions.…”
Section: Influence Of Lpbf Feedstockmentioning
confidence: 99%
“…Recent TEM studies on 316LSS powders fabricated via inert gas atomization 1 , 7 , 24 have revealed the presence of a significant amount of non-oxide precipitates (rich in Mo, Cr, P and S) together with Mn-Si–O precipitates. Interestingly, the maximum cooling rates encountered during inert gas atomization 25 27 are in the same range as those occurring during LMD i.e., 10 2 –10 5 K/s, which suggests that there should be a significant presence of non-oxide precipitates in LMD 316LSS.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that literature reports on the presence of oxides on the surface of atomized AISI316L powders [ 39 ] : in particular, in inert gas atomized powders (as is the case of this work) Fe 2 O 3 , and Cr, Mn, Si oxides are formed. Oxides should be removed to activate the sintering process, diffusivity being higher for oxides than for pure metals.…”
Section: Resultsmentioning
confidence: 68%